A systematic review of quantitative and qualitative literature on health professionals' experiences communicating with Chinese immigrants. Issue 6 (19th May 2021) - Li, Jialin; Lowres, Nicole; Koo, Fung Kuen; Gallagher, Robyn
Abstract: Aim: The aim of this study is to determine health professionals' experiences communicating with Chinese immigrants and identify potential education barriers. Background: Health professionals caring for Chinese immigrants often encounter communication barriers, leading to uncertainty of quality of care. Design: This study is a quantitative and qualitative systematic review. Data sources: MEDLINE, Scopus, CINAHL, PubMed and Google Scholar were searched, limited to 1980 to October 2020. Review methods: Articles were included if they reported results about health professional communication with Chinese patients. Quality was appraised using Consolidated Criteria for Reporting Qualitative Research guidelines and thematic synthesis conducted. Results: Of 1363 articles, seven studies were included. These described provider–patient communication in primary care, oncology and palliative settings only. Three core themes were identified: (1) family‐centred health communication where family controls provider–patient information exchange; (2) mismatch of provider–patient health beliefs and knowledge on diet, nutrition, traditional medicine, place for death and disease prevention and (3) mismatch of language and resources as skilled providers proficient in specific dialects are limited; communication resources are perceived as infrequently available and content is insufficient. Conclusion: Studies describing health professionals' experiences communicating with Chinese immigrants are limited. Key barriers identified included cultural and language disparities and communication resources are inadequate to support health professionals' needs. Summary statement: What is already known about this topic? Health‐care professionals caring for Chinese immigrants are likely to encounter communication barriers. There has not been a systematic examination of the research evidence. What this paper adds? Key barriers identified included cultural and language disparities. Communication resources are inadequate to support health professionals' needs. The implications of this paper: This study is the first systematic review examining health professionals' views and experiences about communicating with Chinese immigrants. Research is needed to explore the experiences and potential patient education barriers of diverse health professionals and their communication needs.